Perovskite CsPbBr3 Quantum Dots Prepared Using Discarded Lead–Acid Battery Recycled Waste - Lung-Chien Chen; Ching-Ho Tien; Sin-Liang Ou; Kun-Yi Lee; Jianjun Tian; Zong-Liang Tseng; Hao-Tian Chen; Hao-Chung Kuo; An-Cheng Sun (Energies, 2019)
Perovskite CsPbBr3 quantum dot (CsPbBr3-QD) recovery was performed using lead scrap from lead storage batteries. The perovskite CsPbBr3-QD characteristics were analyzed using different PbO/recycled PbO2 ratios. Scanning electron microscopy (SEM) was used to observe the film surface morphology and cross-section. High-resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) were used to observe the perovskite CsPbBr3-QDs’ structural characteristics. A photoluminescence (PL) measurement system was used to analyze the optical properties. The results show that lead scrap from lead–acid batteries as a material for perovskite CsPbBr3-QD production can be successfully synthesized. This saves material and also proves that recycling is valuable. The proposed approach is helpful for future material shortages and materials not easily accessible. Although the efficiency is not very high, this process will be purified using recycled lead in the future to achieve higher quantum yield.